Analisis Pengaruh Kualitas Pelayanan dan Produk Tabungan Berbasis Syariah Terhadap Keputusan Menabung Pada CIMB Niaga Syariah Kantor Cabang Solo - Gheza Arsi Afiffudin (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
The purpose of this research is to determine the influence of service quality and sharia-based savings products on savings decisions at CIMB Niaga Syariah Solo Branch Office. This research uses quantitative methods using a questionnaire survey approach. The sample obtained was 118 respondents from CIMB Niaga Syariah Solo Branch Office customers. The data obtained was then analyzed using tests of validity, reliability, normality, heteroscedasticity, multicollinearity, coefficient of determination, t test and F test. From the results of data processing, it shows that the quality of sharia-based savings products influences savings decisions, shown in the t or partial test results. with a calculated t value of 4.410 where the calculated t is greater than the t table of 1.98045 with a significance value of 0.000 < 0.05. From the results of the F or simultaneous test, it can also be seen that the quality of services and sharia-based savings products have a significant influence on savings decisions with a calculated f value of 53.979 where the calculated f is smaller than the f table of 3.08.